TOURIST SATISFACTION WITH RESTAURANTS IN MAJOR CITIES OF THE WESTERN BALKANS - Zivadinovic, Bojan (The European Journal of Applied Economics, 2020)
In the modern world restaurants hold a significant share in achieving a sense of satisfaction in guests, and restaurants in major Western Balkans cities (Belgrade, Zagreb, Ljubljana, Sarajevo, Skopje, Podgorica) are some of the more important factors in satisfying tourism needs of foreign and domestic tourists. Restaurants are places that satisfy daily food and beverage necessities for local inhabitants as well. Hence, the first objective of this paper is to examine the satisfaction expressed by foreign tourists in restaurants of the selected cities in the Western Balkans, and in that sense rate their favourite city. The second objective is to show the degree to which local visitors and domestic tourists are satisfied with services provided in the examined hospitality establishments. The comments which form an integral part of the analysis in the research section of this paper were gathered from one of the most popular websites in the restaurant business field ‒ Trip Advisor.